2015
DOI: 10.4172/2167-0501.1000199
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity and Cytotoxicity of Gold (I) and (III) Ions and Gold Nanoparticles

Abstract: Gold nanoparticles (AuNPs) and gold ion complexes have been investigated for their antibacterial activities. However, the majority of the reports failed to disclose the concentration of free Au(I) or Au(III) present in solutions of AuNPs or gold ion complexes. The inconsistency of antibacterial activity of AuNPs may be due to the effect of the presence of Au(III). Here we report the antibacterial activity of Au(I) and Au(III) to four different bacteria: one nonpathogenic bacterium: E. coli and three multidrug-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 25 publications
(26 reference statements)
4
47
0
1
Order By: Relevance
“…The most used and described method is the chemical synthesis based on the reduction of chloroauric acid by citrate (Lee and Meisel, 1982 ; Fernandes and Baptista, 2017 ). Some studies have addressed the potential of using AuNPs as antibacterial agents, but some controversy still exists (Cui et al, 2012 ; Bresee et al, 2014 ; Shah et al, 2014 ; Shareena Dasari et al, 2015 ; Zhang et al, 2015a ; Shamaila et al, 2016 ).…”
Section: Gold Nanoparticles (Aunps)mentioning
confidence: 99%
“…The most used and described method is the chemical synthesis based on the reduction of chloroauric acid by citrate (Lee and Meisel, 1982 ; Fernandes and Baptista, 2017 ). Some studies have addressed the potential of using AuNPs as antibacterial agents, but some controversy still exists (Cui et al, 2012 ; Bresee et al, 2014 ; Shah et al, 2014 ; Shareena Dasari et al, 2015 ; Zhang et al, 2015a ; Shamaila et al, 2016 ).…”
Section: Gold Nanoparticles (Aunps)mentioning
confidence: 99%
“…Further tests revealed that Au 3+ is the more dominant ion as the bacterial inhibition significantly reduced with gradual removal of Au 3+ ions. The cytotoxicity of Au 3+ increases with concentration, posing possible problems in vivo [ 52 ].…”
Section: Introductionmentioning
confidence: 99%
“…The ferment was incubated with a 1 mM gold salt solution (HAuCl 4 3H 2 O). An optimal incubation time was selected based on some previously published results which demonstrated that gold ions can act as antimicrobial agents at a concentration 1000 times less than the one we were using [37,38] and that they are toxic for bacterial strains such as Escherichia, Staphylococcus, and Salmonella [39]. Taking this into account, all our experiments were performed at two different incubation times: a short period of 2 h and a longer one of 24 h. The formation of AuNPs under these conditions was followed by confirmation with UV-vis spectroscopy and TEM.…”
Section: Biosynthesis Of Gold Nanoparticles By Bacteriamentioning
confidence: 99%